2019
DOI: 10.1001/jamanetworkopen.2019.1549
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Health Care Utilization and Cost of Targeted Drug Delivery and Conventional Medical Management vs Conventional Medical Management Alone for Patients With Cancer-Related Pain

Abstract: IMPORTANCE Targeted drug delivery (TDD) has potential for cost savings compared with conventional medical management (CMM). Despite positive clinical and economic evidence, TDD remains underused to treat cancer pain. OBJECTIVE To assess the cost of TDD and CMM in treating cancer-related pain. DESIGN, SETTING, AND PARTICIPANTS This retrospective economic evaluation using propensity score-matched analysis was conducted using MarketScan commercial claims data on beneficiaries receiving TDD and CMM or CMM only for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…The total reduction in payer annual expenditures associated with opioid discontinuation observed in our study was similar to the previous analysis of commercial claims data (9), when adjusted to align with the 12 months postwashout follow-up used to observe costs in the present study, and inflated to 2017 dollars (15). In another analysis of commercial claims data specific to patients with cancer-related pain, findings also suggested economic benefit among patients treated with intrathecal therapy plus conservative medical management vs. conservative medical management alone, with a significant reduction in payer all-cause costs at 12 months follow-up (mean difference $63,498, p = 0.03) (16).…”
Section: Discussionmentioning
confidence: 97%
“…The total reduction in payer annual expenditures associated with opioid discontinuation observed in our study was similar to the previous analysis of commercial claims data (9), when adjusted to align with the 12 months postwashout follow-up used to observe costs in the present study, and inflated to 2017 dollars (15). In another analysis of commercial claims data specific to patients with cancer-related pain, findings also suggested economic benefit among patients treated with intrathecal therapy plus conservative medical management vs. conservative medical management alone, with a significant reduction in payer all-cause costs at 12 months follow-up (mean difference $63,498, p = 0.03) (16).…”
Section: Discussionmentioning
confidence: 97%
“…The authors suggest that the ICD diagnosis codes for patients receiving an implant were in general rather unspecific (20). A retrospective study using MarketScan commercial claims data identified 1251 patients receiving ITDD for cancer pain between January 2009 and September 2015 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Technological advancements in pain pump technology (patient-controlled analgesia capability, improved catheter design, 40 cc pump reservoir) and evidence supporting the use of spinal medication admixtures (24) have had positive impacts on efficacy of TDD and subsequent improvements in physical function and quality of life (31). TDD has been shown to be a cost-effective alternative to traditional medication management of intractable chronic benign and cancer pain (31)(32)(33). With strong associations between improvement of chronic pain and its positive effect on physical function and quality of life, our results are consistent with reports of previous studies (13,18).…”
Section: Improvements In Pain Physical Function and Quality Of Lifementioning
confidence: 99%